Efeitos de nanopartículas de ouro sobre o tecido ósseo, rim, fígado e coração de ratos - Ruffoni, Leandro Dias Gonçalves (Universidade Federal de São Carlos, 2013)
The process of formation and remodeling of bone tissue is influenced by several factors such as hormones, nutrition, genetics, sex, age, intercurrent disease and environmental factors. There are published reports of the performance of nanoparticles on the development and bone remodeling, and also on kidney, liver and heart. The objective of this study was to analyze the possible influence of gold nanoparticle (AuNPs) exposure on bone tissue and on kidney, heart and liver. After a single intravenous AuNPs exposure biometric, biophysical and biomechanical bone parameters of adult rats were analyzed. The animals were randomly distributed into three groups (1 week, 1 month and 2 months), divided into four, which were respectively treated with polymer poliaminoamida (PAMAM), PAMAM + AuNPs, citrate (citrate buffer) and citrate + AuNPs. Gold nanoparticles were administered by a single dose (0,01 mg Au/kg MC),via the jugular vein. The biomechanical properties of femurs were obtained by the three point bending test. The mass of the kidney, liver and heart were also analyzed. There were no significant differences of the different bone parameters and organs weights among the groups in their respective treatment periods. Therefore, the results indicated that the dose of AuNPs used in this study did not impair the quality of bone tissue as well as the organ weights. These results may help in understanding the possible actions of AuNPs on the bone tissue and organs.
Keywords: Fisiologia; Ossos - fisiologia; Nanopartículas de ouro; Toxicidade; Tecido ósseo; Rim; Fígado; Coração; Gold nanoparticles; Toxicity; Bone; Kidney; Liver; Heart; CIENCIAS BIOLOGICAS::FISIOLOGIA